Perencanaan Jumlah Tenaga Kerja Optimal Untuk Memenuhi Permintaan Beras (Studi Kasus: PT Mujiarto Putri Kembar Sejahtera) - Amortiana, Olivia Lucky; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to determine the optimal number of workers at PT Mujiarto Putri Kembar Sejahtera to meet the increasing demand for rice production. The methods employed include work sampling, data uniformity and adequacy tests, performance rating, normal and standard time calculations, and Work Load Analysis (WLA). The results reveal that most work elements operate within reasonable workload limits, but the packaging section experiences excessive workload of up to 110%, leading to production delays and unmet demand. Based on the WLA results, one additional worker is required in the packaging section, raising the optimal workforce to 18 employees. This adjustment is expected to improve production capacity and balance workload distribution across workstations.